PHYSICAL-MECHANICAL PERFORMANCES OF STEERING WHEEL COVER LEATHERS IN SPECIAL CONDITIONS - MADALINA IGNAT; ANDREI DUMITRU; BOGDAN RUSU; ROXANA CONSTANTINESCU; CIPRIAN CHELARU (Journal of Engineering Studies and Research)
The steering wheel is among the important components of a vehicle, through it having full control over its direction. It is made of a metal base covered with a polymeric material. To improve the look and feel of a steering wheel, usually it is covered by leather. Choosing the material for covering the steering wheel must be done responsibly, because depending on the material, it can generate a certain type of comfort when using the steering wheel. Thus, the current work aims to evaluate the durability and wear resistance of different types of leather coatings used in automotive steering wheels. A series of tests were performed on leather samples before and after exposing them to special conditions (high\low temperature, humidity, UV) like tensile strength and elongation, tear strength, tear load, surface softness, color fastness and flex resistance. All the tests were performed according to actual standards in ICPI accredited laboratory. The results of the experiment showed that the durability and wear resistance of the leather varied significantly depending on the type of coating. Overall, the study provides valuable insights into the characteristics of different types of leather and can help future research involved in developing more durable and long-lasting steering wheel cover leathers.